2021
DOI: 10.1108/jeas-11-2020-0183
|View full text |Cite
|
Sign up to set email alerts
|

Testing cointegration between workers' remittances and human capital formation in Sri Lanka

Abstract: PurposeThis study investigates the long-run relationship between workers' remittances and human capital formation in Sri Lanka by using the macro-level time series data during the period of 1975–2020.Design/methodology/approachIn this study, the augmented Dickey–Fuller (ADF) and Philips–Perron (PP) unit root tests, the autoregressive distributed lag (ARDL) bounds cointegration technique, the Granger causality test, the forecast error variance decomposition technique and impulse response function analysis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Mohamed Aslam and Sivarajasingham [38] investigated the impact of remittances on human capital formation in Sri Lanka by using macro-level, time-series data from 1975-2020. The study documented a positive, statistically significant association between remittances and human capital formation in both the long and short run.…”
Section: Remittance and Human Capital Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohamed Aslam and Sivarajasingham [38] investigated the impact of remittances on human capital formation in Sri Lanka by using macro-level, time-series data from 1975-2020. The study documented a positive, statistically significant association between remittances and human capital formation in both the long and short run.…”
Section: Remittance and Human Capital Developmentmentioning
confidence: 99%
“…According to the existing literature, two studies have measured human capital development with empirical assessments: The Human Capital Development Index [38] and secondary-school enrollment [37]. Adenutsi [37] was the first to examine the link between foreign remittances and human development; in his study, he suggested that remittances had a beneficial influence on human development.…”
Section: Variables Definition and Data Sourcesmentioning
confidence: 99%
“…Additionally, to analyze the causal connection of remittance to education in the short-run, a pairwise Granger causality test is employed. With the null hypothesis of Xt does not Granger cause Yt, the specification can be formed as follows (Granger, 1988;Aslam & Sivarajasingham, 2023):…”
Section: Model Specification and Methodsmentioning
confidence: 99%
“…With increasing emigration, remittances are an important source of capital input in developing countries, and they can serve as both a source of physical and social capital (Chami et al, 2005;Meyer & Shera, 2017;Sinha et al, 2019). Workers' remittance thus, can promote human capital in the short-and long-run (Aslam & Sivarajasingham, 2023). Many studies linked remittance to educational attainment via income, investment, and consumption perspectives.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation